Influence of accommodation units on the visitation of the Plitvice Lakes NP - Jerić, Marijana (Oeconomica Jadertina, 2018)
This paper was dedicated to the research of the accommodation units influence on the visitation of the Plitvice Lakes NP, specifically the analysis of the existence of causative relationship between the independent variables of domestic guests overnight stays at hotels Jezero, Plitvice and Bellevue, foreign guests overnight stays at hotels Jezero, Plitvice and Bellevue, domestic guests overnight stays at Macola Hotel, foreign guests overnight stays in Macola, domestic guests overnight stays in the private accommodation and foreign guests overnight stays in the private accommodation, with a dependent variable of the number of visitors to Plitvice Lakes NP for the period from 2007 to 2017, for a total of five months from May to September. The results of the conducted analysis indicate that the huge importance of estimating the number of visitors to the national park is allocated to the following determinants: the number of foreign guests overnight stays at Macola Hotel, the domestic guests overnight stays in the private accommodation and the foreign guests overnight stays in the private accommodation. In combination with the results of previous research, it was concluded that the accommodation plays a key role in the visitation of the national park.